Conference of West European Members of Parliament on sanctions against South-Africa. F.l.t.r.: Chissano, Sule, Scholten, Kars - Stegeman, Jan,
Conference of West European Members of Parliament on sanctions against South-Africa. F.l.t.r.: Chissano, Sule, Scholten, Kars.